Sequential Emergence of Antibiotic Resistance in Enterococcal Bloodstream Isolates over 25 Years - Murdoch, David R. (American Society for Microbiology, 2002)
We determined the antibiotic susceptibilities of 1,785 enterococcal bloodstream isolates collected over 25 years. Antibiotic resistance emerged at a greater rate in Enterococcus faecium than in other enterococcal species, and E. faecium isolates became proportionally more common over time. Our findings confirm the pattern of emerging antibiotic resistance among enterococci and highlight the increasing importance of E. faecium as a cause of bloodstream infection.